Control of a high gain DC-DC converter based on an active switched-inductor and passive switched- capacitor networks - Kong, Jun Hao (Nanyang Technological University, 2020)
This report presents the implementation of a high gain DC-DC converter based on an active switched-inductor and passive switched-capacitor network and a current controller as its control system. The converter used has a higher DC gain than the conventional boost converter. The control of the converter using a current-mode controller was carried out and its performance was evaluated under different operating conditions. Experimental results showing the features of the controller are also provided.